Advanced informatics for computing research : first International Conference, ICAICR 2017, Jalandhar, India, March 17-18, 2017, Revised selected papers /: first International Conference, ICAICR 2017, Jalandhar, India, March 17-18, 2017, Revised selected papers. (2017) - Unknown
No abstract available